2023
DOI: 10.1111/iwj.14413
|View full text |Cite
|
Sign up to set email alerts
|

Green and eco‐friendly biosynthesis of zinc oxide nanoparticles using Calendula officinalis flower extract: Wound healing potential and antioxidant activity

Cigdem Aydin Acar,
Muhammet Abdurrahim Gencer,
Suray Pehlivanoglu
et al.

Abstract: This study aimed to produce zinc oxide nanoparticles with Calendula officinalis flower extract (Co‐ZnO NPs) using the green synthesis method. In addition, the antioxidant and wound healing potential of synthesized ZnO NPs were evaluated. The absorbance band at 355 nm, which is typical for ZnO NPs, was determined from the UV–Vis absorbance spectrum. The energy‐dispersive X‐ray spectroscopy (EDS) measurements revealed a high zinc content of 42.90%. The x‐ray diffractometer data showed Co‐ZnO NPs with an average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…and Origanum majorana leaf extract (379.75 nm) (18,23). The UV-vis band of ZnO NPs containing Calendula officinalis flower extract exhibited a peak at 355 nm using the green synthesis method (17). SEM images (Figure 3) revealed nano-sized particles of O-ZnO NPs, primarily spherical and irregularly shaped, similar to findings in various biosynthetic ZnO NP studies (16,17,24,25).…”
Section: Antioxidant Activity Of Zinc Oxide Nanoparticlessupporting
confidence: 75%
See 2 more Smart Citations
“…and Origanum majorana leaf extract (379.75 nm) (18,23). The UV-vis band of ZnO NPs containing Calendula officinalis flower extract exhibited a peak at 355 nm using the green synthesis method (17). SEM images (Figure 3) revealed nano-sized particles of O-ZnO NPs, primarily spherical and irregularly shaped, similar to findings in various biosynthetic ZnO NP studies (16,17,24,25).…”
Section: Antioxidant Activity Of Zinc Oxide Nanoparticlessupporting
confidence: 75%
“…-minute incubation on a shaker at 37°C (17). The absorbance of the samples at 517 nm was recorded to estimate the DPPH scavenging activity, calculated using a specific equation.…”
Section: Antioxidant Activity Of Zinc Oxide Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the antibacterial activity of various plants was evaluated by testing their varied solvent extractions against a range of harmful bacteria. It was found that flowers were particularly beneficial in their practical uses [ 31 34 ].…”
Section: Discussionmentioning
confidence: 99%